A Clinical Evaluation of Haritaki Kashaya and Madhu as Kawala in the Management of Post Operative Sore Throat due to Tracheal Intubation Under General Anaesthesia (AYUSHDHARA, 2022)
A sore throat is pain or irritation in the throat. It is usually caused by acute pharyngitis (inflammation of the pharynx). Although it can also appear as a result of trauma, diphtheria or other conditions. Post (Post Operative Sore Throat) is a common complaint in patients undergoing general anaesthesia following orotracheal intubation, with reported incidence of 21-65%. POST ranks among the most frequent subjective complaint after tracheal intubation under general anaesthesia. Post operative sore throat, cough and hoarseness of voice though minor sequel, but they may cause significant post operative morbidity and patient dissatisfaction. Various pharmacological and non-pharmacological trials have been used for attenuating POST with no single proven modality in modern medicine. Keeping this in mind, a thorough study was planned to search out for an ideal Ayurvedic preparation for the management of Post Operative Sore Throat due to tracheal intubation under general anaesthesia. As Haritaki has anti-inflammatory and anti-septic properties and Madhu has anti microbial and wound healing properties, A planned study was done on “Haritaki Kashaya and Madhu as Kawala” to evaluate its importance in treating post operative sore throat caused by tracheal intubation and the results were compared with the patients receiving normal saline gargles. Total effect of drug was evaluated on the basis of signs and symptoms relieved after completion of the trial. The data obtained in clinical study before and after the trial was expressed in terms of Mean, Standard Deviation (SD±) and Standard Error (SE±). Group-II (trial group) revealed better results than Group-I (control group) over total criteria of assessment. The trial drug was found to be efficient to relieve the symptoms like coughing, pain in throat and post operative sore throat in the patients who undergo orotracheal intubation after general anaesthesia